The Rest is Memory - Tuck, Lily, 1938- (New York : Liveright Publishing Corporation, a division of W.W. Norton & Company, 2025)
"First glimpsed riding on the back of a boy's motorcycle, fourteen-year-old Czeslawa comes to life in this ... novel by Lily Tuck, who imagines her upbringing in a small Polish village before her world imploded in late 1942. Stripped of her modest belongings, shorn, and tattooed number 26947 on arriving at Auschwitz, Czeslawa is then photographed. Three months later, she is dead. How did this happen to an ordinary Polish citizen? This is the question that Tuck grapples with in this ... novel, which frames Czeslawa's story within the epic tragedy of six million Poles who perished during the German occupation"--
Keywords: Kwoka, Czeslawa -- Fiction; Auschwitz (Concentration camp) -- Fiction; World War, 1939-1945 -- Fiction. -- Children; Holocaust, Jewish (1939-1945) -- Fiction. -- Poland; Poland -- Fiction. -- History -- Occupation, 1939-1945; Historical fiction; Biographical fiction; Bildungsromans